顎関節部に生じた慢性拡張性血腫の1例 - 樺沢, 勇司; 武元, 徹; 小村, 健; 原田, 浩之; 平井, 秀明; 津島, 文彦 (日本口腔外科学会雑誌, 2016)
We report a case of chronic expanding hematoma (CEH) in the temporomandibular joint (TMJ) region. A 48-year-old man visited our department because of a mass in the left preauricular region and trismus in November 2012. He had noticed the mass about 2 months previously, which gradually expanded. At initial presentation, examination revealed a hard elastic mass, measuring 22 mm in diameter, in the left preauricular region. The maximum mouth opening was 33 mm. Computed tomography showed a well-demarcated mass lateral to the mandibular condyle, accompanied by condylar bone resorption. On magnetic resonance imaging, the mass showed heterogeneous high signal intensity on T1-weighted images and heterogeneous low signal intensity on T2-weighted images. The mass showed mild uptake on 2-deoxy-2- ［18F］ fluoro-D-glucose positron emission tomography. Fine needle aspiration yielded a diagnosis of class I. The clinical diagnosis was a suspected tumor in the left TMJ region. The lesion was extirpated with the patient under general anesthesia in December 2012 and was histopathologically diagnosed as hematoma. On the basis of the clinical course and histopathological findings, the lesion was finally diagnosed as CEH. As of about 3 years after surgery, the postoperative course has been uneventful, with no evidence of recurrence.